PENGARUH KUALITAS PELAYANAN DAN IKLAN TERHADAP KEPUASAN KONSUMEN PADA KONSUMEN OPTIMUM WEDDING ORGANIZER PEKANBARU - M. Yuda Alfarozil; Meyzi Herianto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted at Optimum Wedding Organizer Pekanbaru which is located at Jalan Cendrawasih No.4 Kp. Malay, Sukajadi, Pekanbaru City, Riau. This study aims to determine the effect of service quality and advertising on consumer satisfaction partially and simultaneously. This research uses quantitative descriptive analysis method with SPSS program. The population in this study were all consumers who made purchases or used Optimum Wedding Organizer Pekanbaru products. As well as samples from this study as many as 100 respondents from consumers Optimum Wedding Organizer Pekanbaru. Determination of the sample in this study using the Slovin formula, namely by non-probability sampling technique with accidental sampling technique. Data analysis used validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis and significance test with t test (partial test) F test (simultaneous test). The results of this study indicate the results of the t-test hypothesis of service quality on customer satisfaction, which is seen by t count of 1.865 > t table of 1.660 and significance means that service quality is significant to customer satisfaction. Second, advertising on consumer satisfaction is t count 1.819 > t table 1.660, meaning that advertising is significant to consumer satisfaction. F test results of the implementation of promotions and brand image on purchasing decisions, namely F count = 285.916 > F table = 3.09 Keywords: Service Quality, Advertising, Consumer Satisfaction.